2010
DOI: 10.1159/000275503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Tirofiban and Aspirin in Reducing Short-Term and Long-Term Neurologic Deficit in Patients with Ischemic Stroke: A Double-Blind Randomized Trial

Abstract: Background: Thrombolysis with rt-PA is the only approved pharmacological therapy for acute ischemic stroke presently administrable in a 3-hour window (very recently extended to 4.5 h). After this time, the choice is limited to endovascular treatment and antiplatelet drugs, mainly aspirin (ASA), the efficacy of which in the acute phase of stroke has poorly been evaluated. We compared the efficacy of tirofiban, a GP-IIb/IIIa inhibitor, and ASA, with both drugs being administered within 6 h. Methods: 150 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…31 Because platelet activation is a key step in thromboembolism in the reocclusion of an in situ steno-occlusive lesion, [31][32][33][34] intravenous or intra-arterial glycoprotein IIb/IIIa inhibitors could be effective for preventing reocclusion. 32,34 On the basis of the findings of the Abciximab in Emergency Treatment of Stroke Trial, which showed an increased rate of symptomatic or fatal intracranial hemorrhage, 35 we used intravenous or intra-arterial tirofiban in our study only when no contraindication existed.…”
Section: Discussionmentioning
confidence: 99%
“…31 Because platelet activation is a key step in thromboembolism in the reocclusion of an in situ steno-occlusive lesion, [31][32][33][34] intravenous or intra-arterial glycoprotein IIb/IIIa inhibitors could be effective for preventing reocclusion. 32,34 On the basis of the findings of the Abciximab in Emergency Treatment of Stroke Trial, which showed an increased rate of symptomatic or fatal intracranial hemorrhage, 35 we used intravenous or intra-arterial tirofiban in our study only when no contraindication existed.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of glycoprotein IIb/IIIa receptor blockade in the prevention of infarcts during coronary intervention is well established in the literature [7,8,9,10,11,12,13]. Current studies investigate the efficacy of glycoprotein IIb/IIIa inhibition in the acute phase of stroke [14]. However, evidence for the superiority of the inhibition of platelet adhesion in the prevention of stroke during cerebral DSA is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…GP IIb/IIIa inhibitors have been tested in various protocols for the treatment of acute stroke with varying degrees of success [7,8,15,44,[51][52][53][54]. Our results indicate a low rate of complications in patients treated within the protocol described here and a suggestion of benefit when compared to a mathematically derived comparison group from the NINDS database.…”
Section: Discussionmentioning
confidence: 74%